Explaining industrial importers' commitment from an emerging market perspective: theoretical and managerial insights - Saleh, Md Abu; Ali, Mohammed Yunus; Andaleeb, Syed Saad (© 2014 Emerald Group Publishing Limited, 2016)
This article was published in the Journal of Business and Industrial Marketing [©2014 Published by Emerald Group Publishing Limited.] and the definite version is available at: http://doi.org/10.1108/JBIM-09-2011-0116 The Article's website is at: http://www.emeraldinsight.com/doi/full/10.1108/JBIM-09-2011-0116